2020
DOI: 10.1128/iai.00444-20
|View full text |Cite
|
Sign up to set email alerts
|

Low-Avidity Autoantibodies against Bactericidal/Permeability-Increasing Protein Occur in Gram-Negative and Gram-Positive Bacteremia

Abstract: Antibody autoreactivity against bactericidal/permeability-increasing protein (BPI) is strongly associated with Pseudomonas aeruginosa infection in cystic fibrosis (CF), non-CF bronchiectasis (BE), and chronic obstructive pulmonary disease (COPD). We examined the pathogen-specific nature of this autoreactivity by examining antibodies to BPI in bacteremia patients. Antibodies to BPI and bacterial antigens were measured in sera by ELISA from five patient cohorts (n = 214). Antibody avidity was investigated. Bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Moreover, autoantibodies to BPI correlate with worsening lung function in patients with these diseases (5)(6)(7). While autoantibodies to BPI are found in other disease states, high-avidity autoantibodies are restricted to patients with chronic lung infection with P. aeruginosa (6,48). Given our data that BPI is required for P. aeruginosa immunity in vivo, the serologic findings in CF, BE, or COPD suggest that autoantibodies against BPI might shape a protective niche that enables chronic infection by P. aeruginosa in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autoantibodies to BPI correlate with worsening lung function in patients with these diseases (5)(6)(7). While autoantibodies to BPI are found in other disease states, high-avidity autoantibodies are restricted to patients with chronic lung infection with P. aeruginosa (6,48). Given our data that BPI is required for P. aeruginosa immunity in vivo, the serologic findings in CF, BE, or COPD suggest that autoantibodies against BPI might shape a protective niche that enables chronic infection by P. aeruginosa in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have indicated molecular mimicry as the less likely mechanism. In a cohort of bacteremic patients, we showed that BPI autoantibodies were present in patients with Gram-positive as well as Gram-negative sepsis [ 84 ]. Anti-BPI antibodies in bacteremic patients (acute infections) were of low-avidity [ 84 ], compared to those in CF or bronchiectasis (chronic infections) patients [ 6 , 10 ], suggesting the breaking of tolerance to BPI arises through affinity maturation rather than cross-reactivity to P. aeruginosa [ 10 ] ( Fig.…”
Section: Autoantibodies To Bpi and Their Impact On Bpi-dependent Immunitymentioning
confidence: 99%
“… Apart from the lung infection and its relationship to ANCA, colonic mucosal levels of BPI are increased in IBD patients [ 85 ] and are associated with anti-BPI antibodies in ulcerative colitis patients [ 77 ]. However, while higher BPI protein levels are reported in serum of bacteremia patients, there was no correlation between serum BPI protein levels and anti-BPI IgG responses [ 84 ]. This evidence suggests a requirement of both presence of BPI and chronic infection/inflammation conditions for the BPI autoantibodies to be generated.…”
Section: Autoantibodies To Bpi and Their Impact On Bpi-dependent Immunitymentioning
confidence: 99%
“…The unique properties of this model not only derive from the specific association of lung infection by P. aeruginosa with BPI autoimmunity but also our demonstration of the importance of BPI in clearing this organism in vivo. Interestingly, no relationship was seen between circulating BPI levels and antibodies to P. aeruginosa in a cohort of bacteremic patients (48). This evidence suggests that patients who are susceptible to P. aeruginosa infections are not defective in producing or releasing BPI to combat infections.…”
Section: Discussionmentioning
confidence: 90%